Effects of Foliar Applications of Boron at the Early Vegetative Stages on Plant Growth Parameters of Maize - Ömer Konuşkan; Mehmet Yalçın; Hüseyin Gözübenli (Turkish Journal of Agriculture: Food Science and Technology)
Boron is an important micronutrient for growth and development of crop plants. Plant species differ in their requirement of boron for growth. This study was conducted to determine the effect of boron application on the plant characteristics of maize during early leaf stages. The experiments were conducted in Tel – Kaliş agricultural research area at the Mustafa Kemal University in 2015 and 2016 growing seasons. The field experiments were arranged in a split plot design with three replications. Four boron dosages (control, 4, 6 and 8 mg/m2) were applied at three growing stages (V2, V4 and V2V4 (at V2 and V4 stages in two equal parts) as foliar spray. The results revealed that the effects of foliar application of B were positive but statistically insignificant on plant characteristics. Further researches should be conducted for suitable boron application time at different growth stages of maize.